A critical review on the environmental application of lipopeptide micelles. (November 2021) - Zhu, Zhiwen; Zhang, Baiyu; Cai, Qinhong; Cao, Yiqi; Ling, Jingjing; Lee, Kenneth; Chen, Bing
Graphical abstract: Highlights: Review of biosynthetic mechanisms and generatic regulated lipopeptide production. Summary of metagenome-based approaches for systematic lipopeptide discovery. Assessment of lipopeptide micelles associated decontamination mechanisms. Evaluation on how high salinity and low temperature affect micellar behaviors. Abstract: The importance of lipopeptide micelles in environmental applications has been highlighted. These vessels exhibit various sizes, shapes, and surface properties under different environmental conditions. An in-depth understanding of the tunable assembling behavior of biosurfactant micelles is of great importance for their applications. However, a systematic review of such behaviors with assorted micro/nano micellar structures under given environmental conditions, particularly under low temperature and high salinity, remains untapped. Such impacts on their environmental applications have yet to be summarized. This review tried to fill the knowledge gaps by providing a comprehensive summary of the recent knowledge advancement in genetically regulated lipopeptides production, micelles associated decontamination mechanisms in low temperature and high salinity environments, and up-to-date environmental applications. This work is expected to deliver valuable insights to guide lipopeptide design and discovery. The mechanisms concluded in this study could inspire the forthcoming research efforts in the advanced environmental application of lipopeptide micelles.